Conducting undergraduate research in education : a guide for students in teacher education programs - Palmer, Ruth J.; Thompson, Deborah L. (New york: Routledge, 2022)
"This book offers a student-focused guide to conducting undergraduate research in education and education-related programs, engaging students in the process of learning through research and supporting them to navigate their multidimensional academic programs. Written for undergraduate students in teacher education programs, the book features a range of leading voices in the field who offer a step-by-step guide to all elements of the research process: from conducting a literature review and choosing a research topic, to collecting data and building a research community with peers and mentors. Ultimately, volume editors Ruth J. Palmer and Deborah L. Thompson help model the competencies that students need to succeed, including complex thinking, strategic design, modeling, and persistent iterative practice, while demonstrating how conducting research can help students develop as deep thinkers, courageous researchers, and active participants in their communities of practice. Offering strategic approaches, support, and guidance, this book demonstrates the wider importance of undergraduate research in informing educational practice and policy, as well as understanding schools beyond the classroom context, encouraging active engagement and continued learning progression. Ruth J. Palmer is Emeritus Professor at The College of New Jersey where, as an Educational Psychologist with a teaching/research focus on adolescence, she was a member of the Department of Educational Administration and Secondary Education in the School of Education, and Affiliate Professor in the Department of African American Studies. Deborah L. Thompson is Emeritus Professor at The College of New Jersey where she was a member of the Department of Elementary and Early Childhood Education who taught graduate and undergraduate courses in literacy and children's literature. She also served as an adjunct professor in the Department of Women's, Gender and Sexuality Studies where she taught a course on gender in children's literature"--
Undergraduate research in teacher education : the legacy, the promise, the responsibility / Ruth J. Thompson -- Beginning the investigation : the research question / Sylvia Talia -- Building a foundation for undergraduate research in teacher education : the literature review / Suzanne Lindt and Emily Smith -- The demands of reading, writing, and thinking like researchers / Deborah L. Thompson -- Technology : the all-purpose research tool for discovery, organization, and collaboration / Judi Puritz Cook -- Building essential components of a research project : determining topic, research design, and ethical conduct need / Giang-Nguyen T. Nguyen and Carla J. Thompson -- Data analysis : the heart of the research study / Deborah L. Thompson -- Building a research community with peers, near-peers, and experienced mentors / Catherine L. Packer-Williams -- Report writing for undergraduate research in teacher education : findings and discussion / Arti Joshi and Jody Eberly -- Report writing II : dissemination and emerging innovative approaches / Jody Eberly and Arti Joshi -- Toward excellence in undergraduate research in teacher education programs : practice, persistence, and partnerships / Ruth J. Palmer.
Includes bibliographical references and index.
Keywords: Education